Time Flow in the Natural World: A Theological Perspective - Ciancio, Emanuele (Theology and science, 2020)
We provide a comparison between the concept of time as issued from classical physics and thermodynamics and the concept of time in Christian theology. We investigate in particular the problem of the emergence of the arrow of time in classical physics and compare it with the problem of time flow and irreversibility of history in a biblical perspective. The result of our analysis will allow us to conclude that the same epistemological pattern accounts for the flow of time both in classical thermodynamics and in theology, testifying a deep common thinking structure shared by the two disciplines.